STUDI ANALISIS TERHADAP PRAKTEK BANK ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œTONGOLÃƒÂ¢Ã¢â€šÂ¬Ã‚Â - Amir Mahmud (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2013)
Discussions about halal and haram bank and the interest has been there since the founders of schools so far as there is no break, because each one has a good reason and the arguments are the arguments aqli naqli. The core of the discussion of the issue rests on whether interest was considered usury or not. Included in this issue practices equated with such banks, KSP, KUD, KSU and practices of individuals who do not have a business license. In this regard, institutions similar to banks and the investors who practice in the field, people often refer to it as bannk tongol. This study shows that the money lending transaction between the merchant and Bank tongol consists of four models, namely first, the pattern of transactions directly on the merchant proactive stance. Second, the pattern directly on a proactive transaction tongol Bank. Third, the pattern of direct transactions that are interactive and fourth, the pattern of transactions indirectly through third party services as a justification of the transaction between the merchant and the bank both actual tongol proactive. Bank tongol for communities containing terms mudlarat and benefits, Bank Tongol mudloratnya is often raises issues that become a burden to the customer. The problems referred to as injustice in essence the transaction, financial necessity, cause economic breakdown, the cause is not growing trading business and the creation of indebtedness that never ended. While the benefits are earned by good fortune some traders such additional capital, even others make major capital will become economic resources for them. Therefore, the Bank can not be absolute tongol categorized as usury because it contains social values.